Varovanje in gojenje tise sta obvezni zadolžitvi gozdarjev - Cimperšek, Mitja (Gozdarski vestnik, 2012)
Wanting to encourage interest and concern for yew - a tree species at risk of extinction - we have presented its spiritual and material significance in the past, above all its trace in the history of warfare and consequences of its disappearing from Slovenian forests. We have described the most important yew locations in Europe, modest and poorly studied remains in our territory and listed some reasons contributing to the best conservation of stands in Kozjansko. Using phytocoenological inventories and Ellenberg's ecological indicators we have compared their sites. We have outlined the most important silvicultural measures for protecting, caring for, and stimulating yew expansion in environments with better developed forestry as well as indicated yew's cultural imprint in park art and healing.
Keywords: tisa; Taxus baccata; ecology; ekologija; geografija; geography; naravovarstvo; zdravilstvo; tisovina; lokostrelstvo; gojenje; Kozjansko; Bohor; Bohor reedbuck